The Use of Barbed Suture for Intracorporeal Mechanical Anastomosis During a Totally Laparoscopic Right Colectomy: Is It Safe? A Retrospective Nonrandomized Comparative Multicenter Study. (June 2018) - Bracale, Umberto; Merola, Giovanni; Cabras, Francesco; Andreuccetti, Jacopo; Corcione, Francesco; Pignata, Giusto
Background . A totally laparoscopic right colectomy could be perceived as a more challenging procedure over a laparoscopic-assisted right colectomy owing to the difficulty of intracorporeal anastomosis and the closure of the enterotomy. The aim of this study is to evaluate the safety and efficacy of the barbed auto-locking absorbable suture for the closure of an anastomotic stapler-access enterotomy during a totally laparoscopic right colectomy. Methods . From January 2010 to April 2016, data from patients who had undergone a laparoscopic right colectomy in 2 different departments of 2 institutions (the Department of General and Minimally Invasive Surgery, San Camillo Hospital in Trento and the Department of Surgical Specialties and Nephrology, University Federico II in Naples) were retrospectively analyzed. We compared the data of patients in whom the stapler-access enterotomy was closed through a conventional absorbable suture (Group A), with the data of patients in whom a stapler-access enterotomy was closed through a V-Loc 180 suture (Group B). Biometric features and intraoperative and postoperative data were collected and analyzed. Results . The 2 groups (Group A: 40 patients; Group B: 40 patients) were comparable for biometric features and postoperative outcomes. The anastomosing time was lower in Group B. A statistically significant difference was noted in the mean operative time between Groups A and B (Group A = 134.92 ± 34.17; Group B = 120.92 ± 23.27, P = .035). Only one anastomotic leakage per group was recorded, each treated with an anastomosis redo. During the reoperations, we find in both groups an intact stapler-access enterotomy. Conclusion . On retrospective analysis, barbed suture appears to be safe and efficient for closure of the stapler-access enterotomy during totally laparoscopic right colectomy.